Working around a contested diagnosis: Borderline personality disorder in adolescence. (January 2013) - Koehne, Kristy; Hamilton, Bridget; Sands, Natisha; Humphreys, Cathy
This discourse analytic study sits at the intersection of everyday communications with young people in mental health settings and the enduring sociological critique of diagnoses in psychiatry. The diagnosis of borderline personality disorder (BPD) is both contested and stigmatized, in mental health and general health settings. Its legitimacy is further contested within the specialist adolescent mental health setting. In this setting, clinicians face a quandary regarding the application of adult diagnostic criteria to an adolescent population, aged less than 18 years. This article presents an analysis of interviews undertaken with Child and Adolescent Mental Health Services (CAMHS) clinicians in two publicly funded Australian services, about their use of the BPD diagnosis. In contrast with notions of primacy of diagnosis or of transparency in communications, doctors, nurses and allied health clinicians resisted and subverted a diagnosis of BPD in their work with adolescents. We delineate specific social and discursive strategies that clinicians displayed and reflected on, including: team rules which discouraged diagnostic disclosure; the lexical strategy of hedging when using the diagnosis; the prohibition and utility of informal 'borderline talk' among clinicians; and reframing the diagnosis with young people. For clinicians, these strategies legitimated their scepticism and enabled them to work with diagnostic uncertainty, in a population identified as vulnerable. For adolescent identities, these strategies served to forestall a BPD trajectory, allowing room for troubled adolescents to move and grow. These findings illuminate how the contest surrounding this diagnosis in principle is expressed in everyday clinical practice.